2006
DOI: 10.1111/j.1600-0714.2006.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of apoptosis‐associated genes and pathways in oral cancer cells

Abstract: The effects of different apoptotic stimuli on normal cells and oral cancer cells can be explained by expression of proapoptosis genes, including the gene that encodes CD40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Recently, it has been demonstrated that NME5 was downregulated in several tumor types, including immortalized human urothelial cells, urothelial carcinoma and primary urothelial tumors through microarray (Chapman et al, 2008). However, NME5 gene expression in human oral cancer cell line Tu183 was constitutively higher than that in normal human epidermal keratinocyte cells (Gibson and Shillitoe, 2006). To date, many research concerning the expression and/or the role of NME5 in human pancreatic cancer have seldom been reported.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, it has been demonstrated that NME5 was downregulated in several tumor types, including immortalized human urothelial cells, urothelial carcinoma and primary urothelial tumors through microarray (Chapman et al, 2008). However, NME5 gene expression in human oral cancer cell line Tu183 was constitutively higher than that in normal human epidermal keratinocyte cells (Gibson and Shillitoe, 2006). To date, many research concerning the expression and/or the role of NME5 in human pancreatic cancer have seldom been reported.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, it has been known that a serial changes in the process of apoptosis is also an essential feature of cancer cells (Gibson and Shillitoe, 2006). Apoptotic process involves an intricate cascade of events which is highly regulated (Malaguarnera et al, 2012;Ko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, oral cancer cells (e.g., Tu183 cells) are known to adapt genetic changes that block cell death. Examples of such adaptations include mutations of p53 and upregulation of bcl -2 expression [12] . …”
Section: Discussionmentioning
confidence: 99%
“…Tu183 cells are derived from a squamous cell carcinoma of the tonsil [11] . This epithelial cell line overexpresses bcl-2 and is highly resistant to cytotoxic drugs [12][13][14][15] .…”
mentioning
confidence: 99%